2006
DOI: 10.1161/01.str.0000195129.95220.77
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of Functional Neuromuscular Stimulation in Chronic Stroke Subjects

Abstract: Background and Purpose-Conventional therapies fail to restore normal gait to many patients after stroke. The study purpose was to test response to coordination exercise, overground gait training, and weight-supported treadmill training, both with and without functional neuromuscular stimulation (FNS) using intramuscular (IM) electrodes (FNS-IM). Methods-In a randomized controlled trial, 32 subjects (Ͼ1 year after stroke) were assigned to 1 of 2 groups: FNS-IM or No-FNS. Inclusion criteria included ability to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(63 citation statements)
references
References 31 publications
3
58
0
2
Order By: Relevance
“…The POMA balance subscale may be a useful tool for predicting the occurrence of falls and examining the balance ability of stroke patients. Although its reliability and validity for stroke patients has been reported (CiprianyDacko et al 1997;Corriveau et al 2004;Daly et al 2006), its discrimination capacity and validity for predicting falls has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The POMA balance subscale may be a useful tool for predicting the occurrence of falls and examining the balance ability of stroke patients. Although its reliability and validity for stroke patients has been reported (CiprianyDacko et al 1997;Corriveau et al 2004;Daly et al 2006), its discrimination capacity and validity for predicting falls has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is consistent within the literature for healthy older adults for these measures, as well as other clinical populations. For healthy older adults, ICC ranged between 0.72-0.80 (Faber, Bosscher, & van Wieringen, 2006) and ranged between 0.874 and 0.91 for stroke patients (Canbek, Fulk, Nof, & Echternach, 2013;Daly et al, 2006). Furthermore, similar measures of physical function assessed in dementia specific populations demonstrated similar levels of relative reliability as those reported within this thesis.…”
Section: First Major Findingsupporting
confidence: 54%
“…This study reported that the standard sensory input was the most important factor of inducing plasticity in the spinal circuit for reciprocal inhibition (Perez et al, 2003). Daly et al (2006) reported the improvement of gait and knee flexion coordination in a stroke patient group applied with FES on the neuromuscular system. However, Prado-Mederios et al (2011) reported that there were no significant differences in motor function, gait linear variation, and kinematic variation in comparison between FES and non-FES application in 12 chronic stroke patients who performed gait training with partial weight support through harness.…”
Section: Introductionmentioning
confidence: 95%